High-entropy alloy and preparation method thereof
By preparing Co1.5CrFeNi1.5Ta0.1Mox high-entropy alloy and using vacuum arc smelting and heat treatment processes, the shortcomings in the corrosion resistance and mechanical properties of existing high-entropy alloys are solved, and high-performance applications in marine environments are achieved.
Patent Information
- Application Number
- CN202411549338.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
AI Technical Summary
The existing high-entropy alloys still have shortcomings in corrosion resistance and mechanical properties, and it is difficult to meet the application requirements under severe environmental conditions such as the ocean.
By preparing a high-entropy alloy with the chemical formula Co1.5CrFeNi1.5Ta0.1Mox, and using vacuum arc smelting and heat treatment processes, solid solution and hardening of Ta and Mo elements are achieved, and a dense passivation film is formed to improve corrosion resistance.
It significantly improves the tensile strength, plasticity and corrosion resistance of high-entropy alloys, is suitable for harsh environmental conditions such as the ocean, and is simple in preparation, suitable for large-scale applications.
Smart Images

Figure CN119392082A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of alloy material preparation, and in particular to a corrosion-resistant high-entropy alloy suitable for harsh environmental conditions such as the ocean and a preparation method thereof. Background Art
[0002] High entropy alloys are a type of alloy system composed of at least five alloying elements, with each element being in nearly equal atomic ratios. Compared to traditional crystalline alloys, high entropy alloys have four typical properties: high entropy effect, hysteresis diffusion effect, lattice distortion effect, and cocktail effect, so they have higher strength, hardness, and corrosion resistance.
[0003] Under extreme working conditions such as nuclear energy and marine environment, existing traditional alloys can no longer meet their application requirements, so high requirements are put forward for new structural materials, that is, they need to have excellent mechanical properties and corrosion resistance. However, the existing high entropy alloys are still insufficient in corrosion resistance and mechanical properties. For example, the document "Insights into the passivity and electrochemistry of CoCrFeMnNi high entropy alloy fabricated by underwater laser direct metal deposition" (Corrosion Science, 2024) discloses the passivation research of high entropy alloys in simulated neutral marine environment and acidic microbial corrosion environment, but the alloy preparation method disclosed in the document is suitable for depositing thin films on metal surfaces, with thin thickness and small volume, and it is difficult to apply on a large scale. Therefore, the preparation of a high entropy alloy block with high hardness and strong corrosion resistance has become a technical problem that needs to be solved in this field. Summary of the invention
[0004] In response to the above problems, the present application provides a high entropy alloy, a preparation method and an application thereof to improve the performance of the high entropy alloy.
[0005] Specifically, the above invention object is achieved through the following scheme:
[0006] First, the present application provides a high entropy alloy, whose chemical formula is Co 1.5 CrFeNi 1.5 Ta 0.1 Mo x , different components are composed according to the atomic ratio of the subscript in the chemical formula; the value of x is 0≤x≤0.5; further preferably, the value of x is 0 or 0.1 or 0.3 or 0.5.
[0007] Secondly, the present application provides a method for preparing the above-mentioned high entropy alloy, and the specific steps are as follows:
[0008] 1. According to the chemical formula of high entropy alloy, Co, Cr, Fe, Ni, Ta, and Mo are mixed with various metal raw materials (raw material purity ≥ 99.9%) according to the atomic ratio of 1.5:1:1:1.5:0.1:x (0≤x≤0.5), and the raw materials are placed in the smelting furnace from bottom to top according to the melting point from low to high;
[0009] 2. Use mechanical pump and molecular pump to evacuate to 8×10 -4 Pa~2×10 -3 Pa, and then fill with high-purity argon gas to -0.04MPa~0.05MPa; then perform vacuum arc melting 5~6 times, the melting current is 240A~270A, the arc time of each melting lasts 3min~5min, and electromagnetic stirring is used during melting, and the speed is 2r / s; after the melting is completed, the obtained metal solution is sucked into a copper mold container to obtain an alloy ingot;
[0010] Before smelting the metal raw material, in order to remove the residual air in the furnace, it is preferred to first add a high-purity Ti ingot and smelt it three times, each time for about 60 seconds, then take out the Ti ingot and then smelt the raw material.
[0011] 3. The alloy ingot is subjected to heat treatment and rolling treatment: first, the alloy ingot is kept at 1200°C for 8 hours for homogenization; then, in order to better improve the mechanical properties of the material, the rolling deformation is 70%, and then it is placed in a tubular furnace for solution treatment at 1200°C for 2 minutes, and then aged at 850°C for 3 hours. The cooling method is water quenching, and the above-mentioned high entropy alloy is obtained.
[0012] Compared with the prior art, the alloy material and preparation method thereof provided in this application have the following beneficial effects:
[0013] (1) The chemical formula of this application is Co 1.5 CrFeNi 1.5 Ta 0.1 Mo x The high entropy alloy, under the action of heat treatment and rolling, the Ta and Mo elements with larger grain size are dissolved in the FCC phase matrix, achieving solid solution strengthening and work hardening, and achieving the performance requirements of high strength and high plasticity. At the same time, the dense passivation film formed also significantly improves the corrosion resistance; and the alloy material prepared by the method of the present application is a block material, which can be used on a large scale and has strong processing performance.
[0014] (2) According to the different Mo content in the alloy, Co 1.5 CrFeNi 1.5 Ta 0.1 Mo xThe tensile strength of high entropy alloys is 691MPa~998MPa, the elongation after fracture is 20%~74%, the self-corrosion potential is -80mV~111mV, and the self-corrosion current density is 7.08×10 -8 A / cm 2 ~3.33×10 -7 A / cm 2 . It is significantly better than the current marine high-entropy alloys (such as the alloy disclosed in the document "Microstructure and corrosion behavior of the Ti-V-Cr-Nb high-entropy alloys in 3.5wt%NaCl solution;Corrosion Science, 2023").
[0015] (3) Co prepared in this application 1.5 CrFeNi 1.5 Ta 0.1 Mo 0.3 High entropy alloy has excellent mechanical properties and corrosion resistance, with a tensile strength of 824MPa, an elongation of 54%, and a self-corrosion current density of 7.08×10 -8 A / cm 2 , the self-corrosion potential is 111mV. Compared with other alloys in the system, the self-corrosion current density is smaller and the self-corrosion potential is higher, indicating that Mo 0.3 The alloy has a lower tendency to corrode, and the passivation film formed is more protective, more suitable for harsh environmental conditions such as the ocean, and meets practical application needs.
[0016] (4) The raw materials of the present invention are easy to obtain, the preparation method is simple, and it has excellent mechanical properties and corrosion resistance. It can be applied to seawater environments on a large scale and has broad application prospects in industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a sample picture of the high entropy alloy after grinding and polishing in Example 1 of the present invention.
[0018] Figure 2 This is the X-ray diffraction spectrum of the high entropy alloy in Example 1 of the present invention.
[0019] Figure 3 It is a scanning image of the high entropy alloy in Example 1 of the present invention and the eds image of each element;
[0020] Among them, AD is the alloy material Co prepared in the embodiment. 1.5 CrFeNi 1.5 Ta 0.1 Mo0(Mo0),Co1.5 CrFeNi 1.5 Ta 0.1 Mo 0.1 (Mo 0.1 ), Co 1.5 CrFeNi 1.5 Ta 0.1 Mo 0.3 (Mo 0.3 ) and Co 1.5 CrFeNi 1.5 Ta 0.1 Mo 0.5 (Mo 0.5 ).
[0021] Figure 4 This is a hardness diagram of the high entropy alloy in Example 1 of the present invention.
[0022] Figure 5 This is a diagram of the mechanical properties of the high entropy alloy in Example 1 of the present invention.
[0023] Figure 6 This is the polarization curve of the high entropy alloy in Example 1 of the present invention in a 3.5wt.% NaCl solution. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0025] The component raw materials Co, Cr, Fe, Ni, Ta, and Mo involved in the following examples were all purchased from Hebei Luohong Technology Co., Ltd. with a purity of 99.95%, and all were 3*3mm metal particles; the mass of each raw material in the examples is based on the actual weighed mass.
[0026] Before the smelting experiment begins, each raw material (metal particles) needs to be ultrasonically cleaned (25W) with anhydrous ethanol for 30 minutes to remove impurities in the raw materials, thereby obtaining uncontaminated metal particles and ensuring that there is no interference from other impurities during the experiment.
[0027] The vacuum arc melting furnace was a WK series purchased from Beijing Wuke Optoelectronics Co., Ltd.;
[0028] Example 1 Preparation of multi-component alloy Co 1.5 CrFeNi 1.5 Ta 0.1 Mo x
[0029] Table 1 Mass ratio of each element
[0030]
[0031] In this embodiment, Co 1.5 CrFeNi 1.5 Ta 0.1 Mo x A method for preparing a high entropy alloy (x=0, 0.1, 0.3, 0.5), comprising the following steps:
[0032] 1. As shown in Table 1 above, the six raw materials Co, Cr, Fe, Ni, Ta, and Mo are mixed according to the general formula Co 1.5 CrFeNi 1.5 Ta 0.1 Mo x The molar ratios of the subscripts of the components in the mixture are weighed, where x is 0, 0.1, 0.3, and 0.5, respectively.
[0033] In order to prevent some metal particles from volatilizing due to heat due to their low melting points, all metal particles are stacked in the vacuum arc melting furnace in order from low to high melting points. In this embodiment, the order from bottom to top is Ni, Fe, Co, Cr, Mo, and Ta.
[0034] 2. Before smelting, use a vacuum pump to pump the vacuum degree of the smelting furnace to 8×10 -4 Pa to prevent residual air from oxidizing the alloy during the smelting process; then fill with argon to 0.05MPa, turn on the electromagnetic stirring, set the electromagnetic stirring current to 2.5A (the speed is about 120rpm), and then perform multiple smelting under the argon protection atmosphere to ensure uniform composition, and then melt the molten metal into a copper mold for suction casting to obtain an alloy ingot.
[0035] In this embodiment, 6 meltings were performed, the melting current was 240A, and the arc time for each melting lasted for 5 minutes. This was to prevent the high melting point alloy elements from not being fully melted, and to ensure uniform distribution of the alloy elements. Since the melting speed of metal particles and the fluidity of the metal in liquid state were different during the experiment, stirring was used to ensure uniform composition of the alloy system.
[0036] In this embodiment, before the raw materials are formally smelted, Ti ingots are first added and smelted for 3 times, each time for about 60 seconds, to remove the residual air in the furnace; and then the raw materials are smelted.
[0037] 3. The alloy ingot is kept at 1200°C for 8 hours for homogenization treatment; then the alloy ingot is taken out for rolling with a rolling deformation of 70%, and then the alloy ingot is put back into the tubular furnace for solution treatment at 1200°C for 2 minutes and aging treatment at 850°C for 3 hours, that is, the target high entropy alloy material.
[0038] Rolling deformation = (L-L0) / L; where L is the original thickness of the material and L0 is the thickness after rolling.
[0039] After the above steps, according to the different Mo contents in the raw material ratio in Table 1, the high entropy alloy Co 1.5 CrFeNi 1.5 Ta 0.1 Mo0(Mo0),Co 1.5 CrFeNi 1.5 Ta 0.1 Mo 0.1 (Mo 0.1 ), Co 1.5 CrFeNi 1.5 Ta 0.1 Mo 0.3 (Mo 0.3 ) and Co 1.5 CrFeNi 1.5 Ta 0.1 Mo 0.5 (Mo 0.5 ).
[0040] The micro-Vickers hardness, mechanical properties and corrosion resistance of the high-entropy alloy material prepared in this embodiment were tested. The specific testing method was carried out according to the method disclosed in the reference "Evolution in microstructure, wear, corrosion, and tribocorrosion behavior of Mo-containing high-entropy alloy coatings fabricated by laser cladding" (Corrosion Science, 2021):
[0041] Each high entropy alloy material obtained in the example was polished with 180 mesh, 400 mesh, 800 mesh, 1200 mesh and 2000 mesh sandpaper in turn, and then further polished with a polishing machine to ensure that the metal surface is smooth, scratch-free, bright and bright. Figure 1 As shown, Figure 1 In the embodiment, AD is the alloy Mo0, Mo 0.1 、Mo 0.3 and Mo 0.5 Finally, the samples were ultrasonically cleaned in alcohol and dried before testing.
[0042] Empyrean multifunctional powder X-ray diffractometer was used to perform XRD test on metal materials. The test results are as follows: Figure 2 As shown. Figure 2 It can be found that with the increase of Mo content, Mo0, Mo 0.1 and Mo 0.3The alloy exhibits a single FCC phase. As the Mo content continues to increase, the Mo 0.5 In addition to the FCC phase, the alloy also has an intermetallic compound σ phase, such as Figure 3 As shown in AD, they are Mo0, Mo 0.1 Mo 0.3 and Mo 0.5 EDS element analysis results of the alloy. Among them, Mo0, Mo 0.1 Mo 0.3 The microstructure shows a single phase and the elements are evenly distributed without segregation phase. 0.5 In addition to the FCC phase, there is a second phase, and the Mo element shows obvious segregation, which is consistent with the xrd results.
[0043] The hardness of the high entropy alloy material was tested using the HV-1000BZ automatic turret microhardness tester. Five points were randomly selected on the metal surface and the average value was taken. The test results are shown in the figure below. Figure 4 As shown. Figure 4 It can be found that the hardness increases with the increase of Mo content, from 184HV to 357HV. 0.1 、Mo 0.3 and Mo 0.5 The hardness performance of the alloy and other alloys is compared, and the results are shown in Table 2:
[0044] Table 2 Hardness test results of high entropy alloys and other alloys
[0045]
[0046] It can be seen from Table 2 that Mo 0.3 and Mo 0.5 Compared with the existing alloys, it still has a very high hardness. The three alloys CoCrFeNiMn, 304 stainless steel, CoCrFeNiW 0.5It was prepared in the laboratory of the applicant. The preparation method thereof refers to the contents disclosed in the literature “Effect of Nb-C addition on the microstructure and mechanical properties of CoCrFeMnNi high entropy alloys during homogenisation, Effect of Sn addition on microstructure, hardness and corrosion behavior of CoCrFeNiSnx high entropy alloys in chloride environment, Microstructural evolution, mechanical properties and corrosion resistance of CoCrFeNiW0.5 high entropyalloys with various annealing heat treatment”, all of which are conventional alloys in the art.
[0047] The mechanical properties of the four high entropy alloy materials prepared in the examples were tested using an E44.304-B electronic universal testing machine. The test results are as follows: Figure 5 As shown. Figure 5 It can be found that the strength of the alloy increases with the increase of Mo content, while the plasticity decreases continuously. 0.1 、Mo 0.3 and Mo 0.5 The mechanical properties of the alloy and other high entropy alloys were tested, and the results are shown in Table 3 below:
[0048] Table 3 Mechanical properties test
[0049]
[0050] As can be seen from Table 3, although Mo 0.5 It exhibits the highest tensile strength, but has a lower elongation. 0.3 It showed the best comprehensive performance, with a tensile strength of 824MPa and an elongation of 54%. 0.3 CoCrFeNi, FeMnNiCuCoSn 0.03All three high entropy alloys were prepared in the applicant's laboratory. The preparation methods were disclosed in the literature “Effects of Nb additions on the microstructure and mechanical properties of CoCrFeNi high-entropy alloys, Microstructure and tensile behaviors of FCC Al0.3CoCrFeNi high entropy alloy, Microstructure and tensile properties of FeMnNiCuCoSnx high entropy alloys”.
[0051] The CorrTest electrochemical test system was used to test the corrosion resistance of high entropy alloy samples in a simulated marine environment. The test results are as follows: Figure 6 As shown. Further analysis of Mo0, Mo 0.1 、Mo 0.3 and Mo 0.5 The corrosion resistance of the alloy and other high entropy alloys was tested, and the results are shown in Table 4:
[0052] Table 4 Corrosion resistance test results
[0053]
[0054] As can be seen from Table 4, Mo 0.3 The alloy has the best corrosion resistance, and the minimum value of self-corrosion current density is 7.08×10 -8 A / cm 2 This shows that when corrosion occurs, the slower the corrosion rate of the alloy sample, the self-corrosion potential is 111mV. 2.1The three high entropy alloys of CoAl, CrFeNiCoAlTi were all prepared in the applicant's laboratory. The preparation methods refer to the contents disclosed in the literature “Microstructure and corrosion properties of the low-density single-phase compositionally complex alloy AlTiVCr、Chen JR, Zhang J, Li K, et al.Microstructure and properties of laser surface remeltingAlCoCrFeNi2.1 high-entropy alloy、Soare V, Mitrica D, Constantin I, et al.Influence of remelting on microstructure, hardness and corrosion behaviourof AlCoCrFeNiTi high entropy alloy.”
[0055] This embodiment uses Co 1.5 CrFeNi 1.5 Ta 0.1 High entropy alloy is used as the matrix material, and on this basis, the content of Mo element is adjusted to optimize the alloy composition. During the synthesis process, by precisely controlling the melting conditions, including key parameters such as vacuum degree, protective gas argon, and melting current, a high entropy alloy with excellent mechanical properties and excellent corrosion resistance was successfully prepared. This method provides a comprehensive technical solution to ensure the superior performance of high entropy alloys. In addition, the required raw materials are easily obtained and the preparation process is simple and feasible. This alloy is suitable for important metal parts in the nuclear energy industry, building bridges, and marine environments, thereby expanding the scope of application of high entropy alloys in industry.
[0056] The above is only an example of the present application and is not intended to limit the scope of application of the present application. Those skilled in the art may make various modifications and variations to the present application, and as long as these modifications and variations conform to the basic spirit and principles of the present application, they should be deemed to be within the scope of the claims of the present application.
Claims
1. A high entropy alloy, characterized in that: The chemical formula of the alloy is Co 1.5 CrFeNi 1.5 Ta 0.1 Mo x , x takes the value of 0≤x≤0.
5.
2. The high entropy alloy according to claim 1, characterized in that The value of x is 0, 0.1, 0.3 or 0.
5.
3. The method for preparing a high entropy alloy according to claim 1 or 2, characterized in that: The specific steps are as follows: 1) Take metal raw materials Ni, Fe, Co, Cr, Mo, and Ta according to the chemical formula ratio, and place each metal raw material in a smelting furnace according to the melting point from low to high; evacuate the smelting furnace to 8×10 -4 Pa~2×10 -3 Pa, inert gas is introduced to perform vacuum arc melting; the melting current is 240 A to 270 A, each melting lasts for 3 min to 5 min, and the melting is performed 5 to 6 times in total; the molten metal obtained by melting is passed into a mold, and an alloy ingot is obtained by suction casting; 2) The alloy ingot is kept at 1200° C. for 8 hours, then rolled, and then placed in a tubular furnace for solution treatment at 1200° C. for 2 minutes, and then aged at 850° C. for 3 hours. The cooling method is water quenching, thereby obtaining the high entropy alloy.
4. The method for preparing a high entropy alloy according to claim 3, characterized in that: Step 1) The introduction of inert gas refers to the introduction of argon gas to a pressure of -0.04 MPa to 0.05 MPa.
5. The method for preparing a high entropy alloy according to claim 3, characterized in that: The rolling refers to a rolling deformation of 70%.